Farming support must switch to black smallholders: Focus on urban elite amounts to rural State Capture - Matisonn, John (New Agenda: South African Journal of Social and Economic Policy, 2024)
Job creation in South Africa is an urgent and paramount project and one of the target areas has to be the agricultural sector. Other targeted economic sectors can deliver jobs for urban matriculants and graduates, but JOHN MATISONN argues farming and agro-processing have the potential to provide hundreds of thousands of new jobs for black citizens in rural areas without advanced education as well as for graduates.